A Fuzzy Control System for Temperature and Humidity Warehouse Control - Nova El Maidah; Agfianto Eko Putra; Reza Pulungan (INFORMAL: Informatics Journal, 2016)
A control system is designed to control certain parameters in the system. The desired state maintained is called a steady state. Control actions however may perform something that makes the system experiences a state of overshoot before reaching the steady state. A fuzzy control system can be used to control the system to reach the steady state without overshoot. In this paper, a model of Mamdani's fuzzy inference process is proposed as the basis for this control. MIN operator is used for inference process if there is only one active rule, while MAX operator is used for composition of inferences if there are more than one active rule. A prototype of the fuzzy controller for temperature and humidity achieves an accuracy of 83.33% for temperature controller and an accuracy of 63.33% for humidity controller.